Lessons for inductive germline determination. - Seervai, R.N.; Wessel, G.M. (Molecular Reproduction and Development, 2013)
Formation of the germline in an embryo marks a fresh round of reproductive potential, yet the developmental stage and location within the embryo where the primordial germ cells (PGCs) form differs wildly among species. In most animals, the germline is formed either by an inherited mechanism, in which maternal provisions within the oocyte drive localized germ-cell fate once acquired in the embryo, or an inductive mechanism that involves signaling between cells that directs germ-cell fate. The inherited mechanism has been widely studied in model organisms such as Drosophila melanogaster, Caenorhabditis elegans, Xenopus laevis, and Danio rerio. Given the rapid generation time and the effective adaptation for laboratory research of these organisms, it is not coincidental that research on these organisms has led the field in elucidating mechanisms for germline specification. The inductive mechanism, however, is less well understood and is studied primarily in the mouse (Mus musculus). In this review, we compare and contrast these two fundamental mechanisms for germline determination, beginning with the key molecular determinants that play a role in the formation of germ cells across all animal taxa. We next explore the current understanding of the inductive mechanism of germ-cell determination in mice, and evaluate the hypotheses for selective pressures on these contrasting mechanisms. We then discuss the hypothesis that the transition between these determination mechanisms, which has happened many times in phylogeny, is more of a continuum than a binary change. Finally, we propose an analogy between germline determination and sex determination in vertebrates-two of the milestones of reproduction and development-in which animals use contrasting strategies to activate similar pathways.